2021
DOI: 10.1002/oby.23090
|View full text |Cite
|
Sign up to set email alerts
|

Resting Energy Expenditure: From Cellular to Whole‐Body Level, a Mechanistic Historical Perspective

Abstract: The basis of heat generated by the human body has been a source of speculation and research for more than 2,000 years. Basal heat production, now usually referred to as resting energy expenditure (REE), is currently recognized as deriving from biochemical reactions at subcellular and cellular levels that are expressed in the energy expended by the body’s 78 organs and tissues. These organs and tissues, and the 11 systems to which they belong, influence body size and shape. Connecting these subcellular‐/cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 81 publications
2
24
0
3
Order By: Relevance
“…The same applies to FFM alone or combined with fat mass in REE prediction models. In the present study, we observed that high muscularity was accompanied mainly by a larger liver and kidney mass but not by a larger brain mass, an organ with a high mass‐specific metabolic rate (240 kcal/kg/day) 3 . Resting energy expenditure prediction equations with weight, height and age as covariates have lower R 2 s and SEEs than those that include individual organs and tissues, as do REE prediction equations formulated on fat mass, FFM, and age as covariates 8 .…”
Section: Discussionsupporting
confidence: 39%
See 2 more Smart Citations
“…The same applies to FFM alone or combined with fat mass in REE prediction models. In the present study, we observed that high muscularity was accompanied mainly by a larger liver and kidney mass but not by a larger brain mass, an organ with a high mass‐specific metabolic rate (240 kcal/kg/day) 3 . Resting energy expenditure prediction equations with weight, height and age as covariates have lower R 2 s and SEEs than those that include individual organs and tissues, as do REE prediction equations formulated on fat mass, FFM, and age as covariates 8 .…”
Section: Discussionsupporting
confidence: 39%
“…That is, for the same BMI, body builders have a smaller percentage of body weight as fat mass than their sex‐matched and age‐matched inactive counterparts. Similarly, people of the same sex, age, and body mass but who differ in muscularity will also differ in REE; for the same mass, SM has a three‐fold higher mass‐specific metabolic rate than does adipose tissue 3 . Sparingly little is known about how muscularity and its accompanying physical and metabolic effects vary between people in the general population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, body components including fat mass (FM) and lean tissue mass (LTM) are key contributors of REE. 24 The distribution of body composition differs between sexes in CKD. 25 More importantly, FM per se is closely associated with adipokines levels.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we aimed to explore the independent relationship between circulating adipokines (leptin, adiponectin, and IL-6) and REE. Of note, body components including fat mass (FM) and lean tissue mass (LTM) are key contributors of REE ( 24 ). The distribution of body composition differs between sexes in CKD ( 25 ).…”
Section: Introductionmentioning
confidence: 99%